Study of thalidomide dispensation in the treatment of leprosy by Pharmaceutical Assistance in the Municipality of Araguaína-TO (Research, Society and Development, 2020)
Thalidomide was widely prescribed in the past for its effect against morning sickness in pregnant women, however, many of the children have been affected by their birth defects up to then unknown, a few years after the drug has been used in the treatment of Erythema Nodos um Hansêmico (ENH). The purpose of this study is to analyse the dispensing of thalidomide in the treatment of leprosy by means of the pharmaceutical Assistance (PA), which uses the method in the doctor's office in the municipality of Araguaína-TO. Objective to investigate the delivery and review of the method used, in addition to the review of the treatment of hansen's disease with thalidomide. This is a retrospective review of the medical records pertaining to the dispensation of thalidomide in the treatment of hansen's disease, according to the Pharmaceutical Care in the years from 2013 to 2018. Through this, we have developed a spreadsheet tool for the job, which were obtained from the data of each user is related to the gender, number of patients, age and reactions to questions, and to just draw in the user's profile in the treatment of hansen's disease operated by the pa and highlights the care done in the doctor's office, a pharmacist, is a pioneer initiative in Brazil.